The Refined Consensus Model of Pedagogical Content Knowledge (PCK): Detecting Filters between the Realms of PCK - Franziska Behling; Christian Förtsch; Birgit J. Neuhaus (MDPI AG, 2022)
In this article, we analyse potential filters that moderate the transformation process between the realms of PCK defined in the refined consensus model of pedagogical content knowledge. We tested 58 preservice biology teachers in a 15-week one-group pretest/post-test design. To identify filters between collective PCK (cPCK) and personal PCK (pPCK), we set up moderation models with pretest pPCK as an independent variable, post-test pPCK as a dependent variable, and motivational orientations or professional values as moderator variables. To identify filters between pPCK and enacted PCK (ePCK), we set up moderation models with post-test pPCK as an independent variable, ePCK as a dependent variable, and noticing or knowledge-based reasoning as moderator variables. We did this specifically with a focus on language in biology education. We found that only the variable knowledge-based reasoning had a role as a filter. It moderates the transformation process between pPCK and ePCK (moderation analysis: F(3,19) = 10.40, p < 0.001, predicting 25.72% of the variance). In future studies, other filters should be identified.